Gaucher Disease with Normocytic Normochrome Anemia Manifestation in a 13-Month-Old Baby: A Case Report - Nova Linda; Nice Rachmawati Masnadi; Gustina Lubis; Amirah Zatil Izzah (HM Publisher, 2022)
Background: Gaucher disease is a sphingolipidosis, an inherited disorder of metabolism resulting from glucocerebrosidase deficiency, causing the deposition of glucocerebroside and related compounds. This study aimed to describe Gaucher disease in one year old baby girl. Case presentation: A 13-month-old girl was referred from the district hospital with a diagnosis of hemolytic anemia. The Patient come with major complaints in the form of enlarged abdomen since 6 months ago. The patient looked pale and coughed since 7 days ago, accompanied by a cold. Ultrasound examination of the abdomen shows splenomegaly. Based on supporting examinations, the effect of normocytic normochrome anemia with reticulocytosis was obtained. The bone survey resulted in an Erlenmeyer flask image on both the humerus and femur suitable for Gaucher disease. The results of microscopic evaluation on bone marrow smear found large cells with Gaucher cell characteristics. Laboratory evaluation of glucocerebroside enzymes showed that there was a deficiency deficiency β-glucosidase. Patients get enzyme replacement therapy for 7 times, each therapy is carried out every 2 weeks. Conclusion: Enzyme replacement therapy is the definitive effective therapy in patients with Gaucher disease. Follow-up should, in principle, be individualized, as the heterogeneity of the disease and a number of associated conditions precludes strict protocolized follow-up.